THE INFLUENCE OF BRAND AWARENESS, BRAND IMAGE AND PERCEIVED QUALITY ON BRAND EQUITY SMARTPHONES (Malikussaleh University Economics and Business Student Study) - Radha Chitta Vritti; Rahmaniar; Widyana Verawati Siregar; Muchsin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to analyze the influence of brand awareness, brand image and perceived quality on smartphone brand equity (Study of students at the Faculty of Economics and Business, Malikussaleh University). Data for this research was collected through a survey method using a questionnaire as a data collection instrument. The respondents used in this research were 246 students from the Faculty of Economics and Business, Malikussaleh University. This research uses a quantitative approach with multiple linear regression analysis using SPSS (Statistical Package for the Social Sciences) software. The results of the research show that Brand Awareness partially has a positive and significant effect on smartphone brand equity among students at the Faculty of Economics and Business, Malikussaleh University. Brand image has a positive and significant effect on smartphone brand equity among students at the Faculty of Economics and Business, Malikussaleh University. Perceived quality has a positive and significant effect on smartphone brand equity among students at the Faculty of Economics and Business, Malikussaleh University. Simultaneously brand awareness, brand image and perceived quality have a positive and significant effect on smartphone brand equity among students at the Faculty of Economics and Business, Malikussaleh University.